The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22266/ijies2020.1031.47
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Hash with Convolutional Network for Multi-label Remote Sensing Image Retrieval

Abstract: Recently, deep hashing dominated single label image retrieval approaches. However, the complex nature of remote sensing images, which likely contains multi-labels, hardly benefits from the above approaches. To overcome single-label image retrieval limitations in remote sensing domain, we address this problem by proposing a multi-label remote sensing image retrieval (MLRSIR-NET) framework. Specifically, the proposed MLRSIR-NET composed of two main sub-networks: multi-level feature extraction and deep hash. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In order to verify the validity of the proposed model, we further compared the performance of our method with the existing methods. The method chosen for comparison include ResNet-50, Transformer [49], Swim-Transformer [50], FAH [34], FDRL [47] and MLRSIR-NET [48]. Swim-Transformer adopts a hierarchical structure for adapting images of different scales and implements a linear complexity attention computation using a sliding window approach to optimize the Transformer.…”
Section: ) Comparison Experiments With State-of-the-art Methodsmentioning
confidence: 99%
“…In order to verify the validity of the proposed model, we further compared the performance of our method with the existing methods. The method chosen for comparison include ResNet-50, Transformer [49], Swim-Transformer [50], FAH [34], FDRL [47] and MLRSIR-NET [48]. Swim-Transformer adopts a hierarchical structure for adapting images of different scales and implements a linear complexity attention computation using a sliding window approach to optimize the Transformer.…”
Section: ) Comparison Experiments With State-of-the-art Methodsmentioning
confidence: 99%
“…As it is identified that the single-labeled RSIR methods cannot meet the demand for flexibility and accuracy, and the image is often associated with several real-world concepts, multilabel hashing methods are experimented with. 14,17 A kernel-based feature fusion using supervised hashing is designed to express high-resolution RSI's highly complex geometrical structures and spatial patterns. 29 A hash retrieval strategy that combines hash learning with proxy-based metric learning in a convolutional neural network is presented.…”
Section: Related Workmentioning
confidence: 99%
“…This issue is rectified by the exceptional breakthrough of deep learning (DL) frameworks with the powerful representational ability for features extracted. As a result of the advancement of DL approaches, deep features are utilized in numerous RSIR tasks 14 18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of satellite instruments, the enormous amount of data acquired, and the availability of computational power has enabled a deeper neural network to introduce a new challenges in the earth science domain. 15,16 Recent advances in DL have demonstrated state-of-the-art results in pattern recognition tasks, mainly in image processing and speech recognition. 17,18 Modern convolutional neural network (CNN) architectures [19][20][21] tend to contain enormous hidden layers and millions of neurons, allowing them to concurrently learn hierarchical features for a broad class of patterns from data and achieve well-tailored models for the targeted application.…”
Section: Introductionmentioning
confidence: 99%